Lasso the wind : away to the New West - Egan, Timothy (Alfred A. Knopf, 1998)
"They have tried to tame it, shave it, fence it, cut it, dam it, drain it, nuke it, poison it, pave it, and subdivide it," writes Timothy Egan of the West; still, "this region's hold on the American character has never seemed stronger." In this colorful and revealing journey through the eleven states west of the 100th meridian, Egan, a third-generation westerner, evokes a lovely and troubled country where land is religion and the holy war between preservers and possessors never ends. Egan leads us on an unconventional, freewheeling tour: from America's oldest continuously inhabited community, the Ancoma Pueblo in New Mexico, to the high kitsch of Lake Havasu City, Arizona, where London Bridge has been painstakingly rebuilt stone by stone; from the fragile beauty of Idaho's Bitterroot Range to the gross excess of Las Vegas, a city built as though in defiance of its arid environment. In a unique blend of travel writing, historical reflection, and passionate polemic, Egan has produced a moving study of the West: how it became what it is, and where it is going.